The impact of aggregate fluctuations across the UK income distribution. - Key, Tomas; Lenney, Jamie (Oxford Economic Papers, 2026)
In this article, we examine the response of earnings and employment to fluctuations in aggregate economic activity (GDP) across the income distribution. Using data from the UK's Labour Force Survey, we present evidence that aggregate fluctuations have economically significant but heterogeneous impacts across the income distribution. While the earnings response is broadly similar across the distribution, further decompositions reveal important differences in the channels of transmission. Changes to hours worked and employment better explain the earnings response in the bottom half of the distribution, whereas changes to the hourly wage are more important in the top half. We incorporate these empirical estimates into the calibration of a Heterogeneous Agent New Keynesian (HANK) model for the UK and find that the heterogeneity we document amplifies the consumption response to aggregate shocks by around 10 per cent.